Extracting DICOM metadata from PACS recursively over local network. (September 2016) - Papamichail, Dimitris; Ploussi, Agapi; Kordolaimi, Sofia; Saradeas, Ioannis; Kelekis, Nikolaos L.; Efstathopoulos, Efstathios P.
Abstract : Introduction: Explosive growth in the number of biomedical images in recent years requires new techniques to manage the information collected. Picture archiving and communication systems (PACS) can address the image data management issue, but PACS generally lack any methods for searching images and querying the metadata based on Database Management System (DBMS) records. Purpose: The objective of this study is to develop an automated method to address the problem of requiring DICOM metadata from PACS over local network. Materials and Methods: Algorithms have been developed in JAVA to query the specified DICOM files from the PACS server and extract all metadata. The application allows users to query the metadata of a specific group of patients. The extracted information is automatically formatted and presented to the authorized end user as a Microsoft Excel file for data and further trend analysis. This project has placed increasing emphasis on the security aspect of patient's personal data by encrypting the data over network transmission. Results: A client application has been designed to make requests to the database of the remote server. The integrity and time efficacy of the method has been evaluated with a test sample of 171 DICOM files, while the accuracy of the data has been manually validated. Conclusion: We believe that we have created a useful and time efficient tool for extracting the image metadata from PACS using a remote computer within local network. The simplicity and the compatibility of the application allows any untrained user to exploit this new technology. Disclosure: None.